(untitled) (Journal of Partial Differential Equations, 2000)
In this paper, we study the lower bounds problem for the existence time or solutions to the different massive Dinac-Kiein-Gordon equations and with different massive Klein-Gordon equations, in one space dimension, for weakly decaying Cauchy data, of size ε. The results assert that the existence time is (almost) larger than ε^-4.